Nano-encapsulation of polyphenols in starch nanoparticles: fabrication, characterization and evaluation. Issue 14 (29th June 2022) - Lian, Fengli; Gong, Ersheng; Liang, Hanni; Lin, Yanyun; Chen, Jun; He, Yunxia; Hebelstrup, Kim Henrik; Xia, Wen
Abstract : Nanoparticles are more promising than microcapsules as drug carriers because they can be absorbed directly by intestinal epithelial cells, significantly increasing the uptake and bioaccessibility of polyphenols. Abstract : Nanoparticles are more promising than microcapsules as drug carriers because they can be absorbed directly by intestinal epithelial cells, significantly increasing the uptake and bioaccessibility of polyphenols. Our study aimed to use catechin (CC), epicatechin (EC) and proanthocyanidin (PAC) adsorption onto tapioca starch nanoparticles (TSNs), which were prepared by a physical method. These TSN loaded-polyphenols were subjected to adsorption kinetic, adsorption isotherm, adsorption capacity, antioxidant activity, and in vitro release analyses. The maximum adsorption capacities of TSNs for CC, EC and PACs were 179.39 mg g −1, 109.29 mg g −1 and 287.19 mg g −1, respectively. The adsorption dynamics and isotherms of polyphenols on TSNs conformed well to the pseudo-second-order kinetics and the Freundlich isotherms. Moreover, TSN loaded-polyphenols have low cytotoxicity and can continuously be released under stimulated gastric and intestinal conditions. Antioxidant activity tests showed that TSN loaded-polyphenols can remarkably scavenge DPPH free radicals; the IC50 of TSNs-CC, TSNs-EC and TSNs-PAC were 16.11, 16.59 and 16.93 μg mL −1, respectively.